Navigating great power competition in the 21st century: beyond the cold war paradigm - Kausikan, Bilahari (2023)
Russian aggression against Ukraine and US-China strategic competition have made the world more uncertain and dangerous. But as we grapple with the complexities of Ukraine and the US-China rivalry, it is crucial not to lose the psychological poise needed to put them in proper perspective.